ANALYSIS OF THE APPLICATION OF SIMPLE FINANCIAL ACCOUNTING TO IMPROVE THE EFFICIENCY OF MSME FINANCIAL MANAGEMENT - Anggraini, Anggun; Ruhiyat, Endang; Indawati, Indawati (International Journal of Engagement and Empowerment (IJE2), 2024)
Good financial management is a crucial factor in the success of Micro, Small, and Medium Enterprises (MSMEs), which contribute significantly to the Indonesian economy. However, many MSMEs, including those managed by Yayasan Darul Anwar Banten, need help in structured financial recording, which impacts cash flow management and business decision-making. This research aims to provide counseling and training on effective, simple financial record-keeping for MSMEs. The methods used include interviews, lectures, and evaluation through pre-tests and post-tests to measure participants' understanding. The training results showed that 80% of participants experienced increased knowledge about recording and preparing financial statements. The conclusion of this activity emphasizes the importance of continuous training in financial management to improve the operational efficiency of MSMEs. Suggestions include the need for constant counseling and soft skills development to support the ability of MSMEs to face industry challenges